Mechanistic Projection of First‐in‐Human Dose for Bispecific Immunomodulatory P‐Cadherin LP‐DART: An Integrated PK/PD Modeling Approach. Issue 3 (21st July 2016) - Chen, X; Haddish‐Berhane, N; Moore, P; Clark, T; Yang, Y; Li, H; Xuan, D; Barton, HA; Betts, AM; Barletta, F
Abstract : A bispecific immunomodulatory biotherapeutic molecule (P‐cadherin LP‐DART) based on the Dual Affinity Re‐Targeting (DART) scaffold has been developed as a potential antitumor treatment showing efficacy in preclinical testing. A minimal anticipated biological effect level (MABEL) approach was applied to project the first‐in‐human (FIH) dose, because of its immune agonistic properties following target engagement. The pharmacological activity of P‐cadherin LP‐DART is driven by binding to both P‐cadherin on the tumor cells and CD3 on T cells. Therefore, the concentration of the tri‐molecular synapse formed between drug, T cell, and tumor cell, rather than drug concentration, is responsible for efficacy. A mechanistic pharmacokinetic/pharmacodynamic (PK/PD)‐driven approach was explored to understand the exposure–response relationship based on the synapse concentration to project the MABEL dose. Orthogonal approaches including PK‐driven and receptor occupancy calculations were also investigated. This study showcases the application of PK/PD modeling in immune‐oncology, and could potentially be implemented for other bispecific biotherapeutics .